The Teachings of Dayanat and Qada’ given in the Hadith Literature In the Context of the thoughts of Molana Anwar Shah Kashmiri - Hafiz Muhammad Rasheed; Muhammad Irfan (jihat-ul-islam, 2021)
Hadith is the second basic source of Islamic Jurisprudence and it plays a primary role, after Quran, in the formation of social and legal structure of a society. Society is a group of people of different attitudes. Some people are full of care, love, peace seekers, pious, noble and true gentlemen while some are full of hatred, envy, arrogant and tyrants. Islam guided to maintain peace in society through two ways, Dayanat and Qada’. People live together and set their issues and disputes by themselves, this is called Dayanat, and if they fail to resolve their clashes by themselves, then every society has established an institution named judiciary, this is called Qada’. According to the prominent Islamic scholars, a matter that brings in court is described as Qada’ and before bringing in court it is Dayanat. Molana Anwar Shah Kashmiri is a renowned name in Islamic World. His work on Quran, Hadith, Fiqh and Tasawwaf have been compiled by his pupils in number of books. He showed his uniqueness among his contemporaries through his work in said subject. He hinted that now a days, most of scholars made no differences in qada’ and dayanat, so they could not find the true command of these issues. He differed from other prominent scholars and presented his own findings on dayanat and qada’. The basic questions are, what is dayanat and qada’ according to Molana Kashmiri? Can a judge make a Fatwa and a Mufti make a judicial order to Molana Kashmiri? What is the exclusivity of Moalana Kashmiri in dayanat and qada’? In this article, those principles will be discussed in analytical method Which Molana Anwar Shah Kashmiri applied in describing dayanat and qada’.